Optimalisasi Konseling Individu dan Kelompok untuk Keberhasilan Siswa - Zainal Abidin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Essentially, not all students can do their school tasks well and authentically because some of them may face many problems of life which certainly affect for their study. Therefore, it is necessity that some students do need intensive guidance for their success in both study and life. In addition, to get success for all students without any exception the councelors should apply individual and collective guidance. If all students can solve their problems, so they can study well; and consequently, they have many chances to get success in study that will support the success in life. This paper is focused on elaborating the role of guidance and couceling, either individually and collectively, for studentsâ€™ success.Â Â